Growth and reproductive ecology of Larix laricina in interior Alaska - Brown, Kevin R.
Larix laricina in Alaska occurs on sites ranging from productive slopes and riverbottoms to wet bogs underlain by permafrost. It is largest on sites without permafrost, where it is associated with Picea glauca, but is much more common in bogs, where it occurs with Picea mariana. In this study, I describe the environment of different Larix habitats; compare growth and reproduction of Larix on different sites; and compare the ecology of Larix with the associated Picea species. Larix is a deciduous conifer; however, some needles on juvenile Larix, usually on new shoots, are retained during the winter and function the following spring. This habit may conserve carbohydrates and nutrients. Browsing damage to seedlings by snowshoe hares is common. Larix in bogs die younger than those in warm uplands or riverbottoms; the maximum ages observed in each were 71, 87, and 127 years, respectively. Maximum height and diameter growth rates of Larix were as great or greater than in uplands or riverbottoms, but the duration of rapid growth was twice as long in upland and four times longer in riverbottom trees (90-100 years), resulting in their greater size. Cone production and seed viability of Larix vary between stands and from year to year. Maximum annual cone production among 10 cone crops observed was 1.97 x10⁵ cones ha⁻¹; the highest seed viability was 60 percent. When stand cone production was high, cone production of individual trees was strongly correlated with tree size. Seeds mature by mid-August and disperse beginning in late August to early September. Ninety-five percent of viable seed at one stand fell by November 1. Germination in the laboratory is inhibited at or below 10 deg C. At 12 and 15 deg, germination is stimulated by long photo-period and stratification period; this stimulation decreases at higher temperatures. Natural germination occurs after soils warm and summer rains begin. In riverbottoms, germination is better on mineral seedbeds than feathermoss, possibly due to a better moisture regime. In tussocky ...